Differential Visual Processing of Animal Images, with and without Conscious Awareness - Zhu, Weina; Drewes, Jan; Peatfield, Nicholas A.; Melcher, David (Frontiers in Human Neuroscience, 2016)
The human visual system can quickly and efficiently extract categorical information from a complex natural scene. The rapid detection of animals in a scene is one compelling example of this phenomenon, and it suggests the automatic processing of at least some types of categories with little or no attentional requirements (Li et al., 2002;2005). The aim of this study is to investigate whether the remarkable capability to categorize complex natural scenes exist in the absence of awareness, based on recent reports that “invisible” stimuli, which do not reach conscious awareness, can still be processed by the human visual system (Pasley et al., 2004;Williams et al., 2004;Fang and He, 2005;Jiang et al., 2006;Jiang et al., 2007;Kaunitz et al., 2011a). In two experiments we recorded ERPs in response to animal and non-animal/vehicle stimuli in both aware and unaware conditions in a continuous flash suppression (CFS) paradigm. Our results indicate that even in the “unseen” condition, the brain responds differently to animal and non-animal/vehicle images, consistent with rapid activation of animal-selective feature detectors prior to, or outside of, suppression by the CFS mask.